(untitled) (International Congress on Economics, Management and Business Studies, 2026)
Since independence, the Republic of Uzbekistan has been transforming its centrally planned economy into a market-oriented system, and commercial banks have become one of the key institutions in this process. They mobilize savings, provide credit, support investment projects, and ensure the smooth functioning of the payment system. Because capital markets in Uzbekistan are still developing, bank-based intermediation remains the dominant source of external finance for enterprises and households. The aim of this thesis is to briefly analyze the role of commercial banks in the economy of Uzbekistan, focusing on financial intermediation, investment financing, payment services, and the main challenges facing the sector. The relevance of the topic is explained by the rapid growth of banking assets and loans, the expansion of non‑cash payments, and the ongoing reforms to improve competition and financial stability.